Penguatan Pendidikan Karakter Melalui Permainan Tradisional Di Sekolah Dasar Muhammadiyah Se-Kecamatan Depok - Suyitno, Suyitno; Setyawan, Feri Budi (Universitas Muhammadiyah Magelang, 2021)
Traditional games are one of the cultural assets that have the characteristics of a nation's culture, character education can be formed through traditional games from an early age. This study aims to determine: 1) Implementation of strengthening character education through traditional games at Muhammadiyah Elementary School in Depok District. 2) School efforts to improve the strengthening of character education through traditional games at Muhammadiyah Elementary Schools in Depok District. This research is a field research or field research, with the type of qualitative research. The data presentation was carried out descriptively with the method of observation, interview and documentation. Data analysis refers to Miles and Huberman's model by collecting data, reducing data and presenting data. The results of this study are 1) Implementation of strengthening character education through traditional games at Muhammadiyah Elementary Schools in Depok District is carried out in local content lessons contained in RPP 2) School efforts to improve the strengthening of character education through traditional games at Muhammadiyah Elementary School in Depok District namely by providing infrastructure support used for traditional games